Abnormal Uterine Bleeding (AUB) at Haji Adam Malik General Hospital, Medan, North Sumatera, Indonesia - Putri Ardina Sari Nainggolan; Muhammad Rusda; Dwi Faradina; Aridamuriany Dwiputri Lubis (Majalah Obstetri & Ginekologi, 2023)
HIGHLIGHTS Leiomyoma is still the most common case in women aged 41–50 years. Women who have an obese BMI are the main risk factor for abnormal uterine bleeding, so it is urged for women to maintain an ideal weight because it can be bad for health.   ABSTRACT Objective: This study identified the incidence of Abnormal Uterine Bleeding (AUB) at Haji Adam Malik General Hospital, Medan, Indonesia, in 2020-2021. Materials and Methods: This was a descriptive study with a cross-sectional design. Sampling was taken using total sampling and using retrospective data in the form of medical records with a diagnosis of AUB at Haji Adam Malik General Hospital Medan in 2020–2021. Results: There were 197 cases of AUB, with the highest distribution in the age group of 41–50 years with 84 people (42.6%). The most cases of AUB with an obese BMI were 91 people (46.2%), married status as many as 176 people (89.3%), had the last education level of senior high school as many as 99 people (50.3%), 144 people (73.1%) got their first menstruation when they were >12 years old, 80 people (40.6%) had multiparity, 90 people (45.7%) received medical therapy. Based on the PALM-COEIN classification, the most AUB cases were AUB-L with 99 people (50.3%). Based on the classification of AUB-L locations, most locations were submucosa with 38.6%. Conclusion: AUB-L cases were still the most common cases at Haji Adam Malik General Hospital, Medan, Indonesia, in 2020–2021.